2022
DOI: 10.3389/fcell.2022.949196
|View full text |Cite
|
Sign up to set email alerts
|

S6 kinase 1 at the central node of cell size and ageing

Abstract: Genetic evidence in living organisms from yeast to plants and animals, including humans, unquestionably identifies the Target Of Rapamycin kinase (TOR or mTOR for mammalian/mechanistic) signal transduction pathway as a master regulator of growth through the control of cell size and cell number. Among the mTOR targets, the activation of p70 S6 kinase 1 (S6K1) is exquisitely sensitive to nutrient availability and rapamycin inhibition. Of note, in vivo analysis of mutant flies and mice reveals that S6K1 predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 133 publications
0
11
0
Order By: Relevance
“…As mentioned above, two separate two-hybrid screenings identified POLDIP3 as a major binding partner for S6K1 and ERH, respectively [ 6 , 7 ]. S6K1 is an important downstream target of mTOR and plays a critical role in regulating protein translation and cell size [ 18 ]. In response to insulin stimulation, Richardson and colleagues showed that the hyper-phosphorylated S6K1 binds POLDIP3 and phosphorylates it at serine-383 and serine-385 both in vitro and in vivo to regulate the cell size [ 6 ].…”
Section: Poldip3 Functions In a Variety Of Rna-related Cellular Proce...mentioning
confidence: 99%
“…As mentioned above, two separate two-hybrid screenings identified POLDIP3 as a major binding partner for S6K1 and ERH, respectively [ 6 , 7 ]. S6K1 is an important downstream target of mTOR and plays a critical role in regulating protein translation and cell size [ 18 ]. In response to insulin stimulation, Richardson and colleagues showed that the hyper-phosphorylated S6K1 binds POLDIP3 and phosphorylates it at serine-383 and serine-385 both in vitro and in vivo to regulate the cell size [ 6 ].…”
Section: Poldip3 Functions In a Variety Of Rna-related Cellular Proce...mentioning
confidence: 99%
“…mTORC1 promotes anabolism and inhibits catabolism for cell growth and division. Protein synthesis is enhanced by mTORC1 mainly through the phosphorylation of ribosomal S6 kinases (S6K) and eIF4E binding protein (4E‐BP) for the initial stage of messenger RNA translation 12,13 . Autophagy, a cellular catabolism process and highly conserved defense response, plays important roles in multiple viral infections and replication under mTORC1 regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Protein synthesis is enhanced by mTORC1 mainly through the phosphorylation of ribosomal S6 kinases (S6K) and eIF4E binding protein (4E-BP) for the initial stage of messenger RNA translation. 12,13 Autophagy, a cellular catabolism process and highly conserved defense response, plays important roles in multiple viral infections and replication under mTORC1 regulation. Autophagy initiation induces the formation of a double-membrane structure in the cytoplasm to encapsulate metabolites to develop autophagosomes.…”
mentioning
confidence: 99%
“…Upon amino acid sufficiency, the MTOR complex 1 (MTORC1) kinase enhances translation initiation. The RAG GTPases recruit MTORC1 to the lysosomal surface where it is activated further by RHEB (Ras homolog enriched in brain) GTPase downstream of the TSC (tuberous sclerosis complex) protein complex that integrates growth factor signals coming from AKT and MAPK (mitogen activated protein kinase) signaling (Alesi and Henske, 2022; Battaglioni et al, 2022; Fumagalli and Pende, 2022; Inoki and Guan, 2022; Valvezan and Manning, 2019). Withdrawal of amino acids, including arginine, leucine, methionine, glutamine and asparagine, is known to inactivate MTORC1 through inhibition of the RAG GTPases (Deleyto-Seldas and Efeyan, 2021) and other lysosomal regulators (Hesketh et al, 2020; Melick and Jewell, 2020; Meng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%